Representation of Moral Messages in the Film “KKN di Desa Penari” (Roland Barthes Semiotics Analysis) - Sembiring, Dinda Arwilda; Alfikri, Muhammad; Muary, Rholand (International Journal of Cultural and Social Science, 2023)
A good film is not only used as a medium of entertainment, but must also include education for those who watch the film. In addition, the storyline of the film can convey important information. In the film, of course, there is a moral message that can be used as a lesson after watching the film. The film used as research by researchers is the KKN film in the Dancer Village. The film KKN Di Desa Penari is a film from Indonesia directed by Awi Suryadi and the producer, MD Pictures. This film tells the story of a number of students who carry out KKN activities in a remote village that is still thick with ancestral traditions. Because they broke the rules and committed indecent acts in the village, they must accept the consequences and be held responsible for their actions. This study aims to find and know the moral message packaged by the director in the KKN Di Desa Penari film. This research is a descriptive qualitative research, in which this study will analyze, record, describe and interpret the meaning of the signs and symbols found in the KKN Di Desa Penari film about the meaning of moral messages. The theory used in this study is the semiotic analysis theory of Roland Barthes's model.